NIVEAU DE CONTAMINATION EN POLYCHLOROBIPHENYLES (PCB) DANS LES POISSONS FRAIS PECHES DANS LA LAGUNE DE GRAND-LAHOU (CÔTE D’IVOIRE) - Hampoh Adé Hortense; Ehouman Ano Guy Serges; Brou Kouakou; Traore Karim Sory; Kone Mamadou; Dembele Ardjouma (European Scientific Journal, ESJ, 2014)
Aquatic environments are one of the largest reservoirs of environmental pollutants. This study aimed to evaluate the level of contamination in polychlorinated biphenyls (PCBs) of fishes caught in the lagoon of Grand-Lahou. Three species of fish, carp (Sarotherodon melanotheron), mullet (Mugilcurema) and catfish (Chrysichthys nigrodigitatus), were sampled according to their weight. Indicators PCBs (PCBis) analysis was performed by Gas-Chromatography coupled to an Electron Capture Detector (GC-ECD). Results showed that fresh fishes present concentrations in PCBis ranging from 0.06 to 365.33 ng/g of fresh weight (fw). The highest concentrations are found in cap and catfish species weightingfrom201 to 300 g and in mullet specie weighting from 101 to 200g. The predominant PCBis found in tissues are CB 138, CB 153 and CB 180.The Sum of the seven PCBis per specie shows that the catfish is more contaminated (311.51±208.46 ng/g wf) than the mullet and carp (85.33±58.87and 19.55 ±11.25 ng/g wf respectively).Concentrations in PCBis generally determined in the various species are lower than the Maximum Residue Limit (MRL) of the European- Union regulation (EU/1259/2011). However, catfish weighting more than 100gand mullet between101 and 200g have contamination levels exceeding the MRL. In conclusion, this study showed that the levels of contamination in PCBis of fishes caught in the lagoon of Grand-Lahou vary according to the specie and weight of fishes.